2017
DOI: 10.1038/s41598-017-04470-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Contrast Enhanced Pulmonary Computed Tomography Angiography for the Detection of Angioinvasive Pulmonary Aspergillosis in Immunocompromised Patients

Abstract: Invasive pulmonary aspergillosis (IPA) is one of the major complications in immunocompromised patients. The mainstay of diagnostic imaging is non-enhanced chest-computed-tomography (CT), for which various non-specific signs for IPA have been described. However, contrast-enhanced CT pulmonary angiography (CTPA) has shown promising results, as the vessel occlusion sign (VOS) seems to be more sensitive and specific for IPA in hematologic patients. The aim of this study was to evaluate the diagnostic accuracy of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
(40 reference statements)
0
20
0
3
Order By: Relevance
“…High-resolution CT pulmonary angiography (CTPA) can detect angio-invasion and vessel occlusion signs (VOS). VOS has been shown to be superior to classic CT signs observed in non-contrast enhanced studies to diagnose invasive pulmonary aspergillosis in immunocompromised patients, including those with hematologic malignancies and other causes, with a sensitivity of 0.94, specificity of 0.71 and a diagnostic odds-ratio of 36.8 [ 54 ].…”
Section: Radiological Diagnosismentioning
confidence: 99%
“…High-resolution CT pulmonary angiography (CTPA) can detect angio-invasion and vessel occlusion signs (VOS). VOS has been shown to be superior to classic CT signs observed in non-contrast enhanced studies to diagnose invasive pulmonary aspergillosis in immunocompromised patients, including those with hematologic malignancies and other causes, with a sensitivity of 0.94, specificity of 0.71 and a diagnostic odds-ratio of 36.8 [ 54 ].…”
Section: Radiological Diagnosismentioning
confidence: 99%
“…In patients with haematological malignancies, computed tomography pulmonary angiography (CTPA) has been shown to detect vessel occlusion sign (VOS) [35,36], which provides direct evidence of an angioinvasive process. Recently, Henzler et al [37] suggested that CTPA may also be a very sensitive and specific radiological test for SOT recipients, as VOS in non-neutropenic patients was the strongest radiological predictor of IA.…”
Section: Epidemiology and Diagnosis Of Imimentioning
confidence: 99%
“…Один из основных методов диагностики -КТ органов грудной клетки, специфичные проявления при этом -симптом «серпа» (2,2%), симптом «матового стекла» (11%) и формирование полостей (24,5%) [34]. По данным нашего регистра, наиболее частыми КТ-признаками были симптом «матового стекла» наряду с инфильтративными изменениями -37,5% и симптом «серпа» -12,5%.…”
Section: рисунокunclassified
“…Известно, что симптом «серпа» не характерен для пациентов с нейтропенией, но может появляться в периоде восстановления лейкопоэза [15]. Дополнительным методом диагностики служит КТ-ангиография, которая позволяет диагностировать признаки сосудистой инвазии и окклюзии; чувствительность и специфичность этого метода -0,94 и 0,71 соответственно [34]. Использование позитронно-эмиссионной томографии с 18F-фтордезоксиглюкозой не позволяет в полной мере дифференцировать ИА легких от других воспалительных очагов или метастатического поражения [35].…”
Section: рисунокunclassified